ELECTRIC CHARGE. COULON'S LAW. ELECTROSCOPE. ELECTRIC FIELD. ELECTRIC FIELD LINES OF FORCE - Khatamova Adolatkhan Sultanbek's daughter; Orinboyeva Kumushoy is the daughter of Sultanbek (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2023)
An explanation of a general electrical topic and its wide application. Use of different methods during the lesson.